(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Among the various methods of water purification from oil pollution, an active magnetic method using powder sorbents with ferromagnetic properties is taking its place. The main components of the sludge are ferromagnetic sorbent, oil and water. The paper discusses some methods of using sludge extracted from water during its cleaning from oil pollution, regeneration and reuse of the sorbent. Particularly, recommendations on the use of sludge as an active fuel additive are given. The possibility of using sludge as a filler for oxygen-flux cutting of concrete and in the production of road-building materials is another demonstrated possibility.